Teaching Medical Informatics to Biomedical Engineering Students: Experiences over 15 Years - Wigertz, O.; Persson, J.; Ahlfeldt, H. (Methods of Information in Medicine, 1989)
The Departments of Biomedical Engineering and Medical Informatics at Linkoping University in Sweden were established in 1972-1973. The main purpose was to develop and offer courses in medicine, biomedical engineering and medical informatics to students in electrical engineering and computer science, for a specialization in biomedical engineering and medical informatics. The courses total about 400 hours of scheduled study in the subjects of basic cell biology, basic medicine (terminology, anatomy, physiology), biomedical engineering and medical informatics. Laboratory applications of medical computing are mainly taught in biomedical engineering courses, whereas clinical information systems, knowledge based decision support and computer science aspects are included within the medical informatics courses.
Keywords: Medical Informatics; Biomedical Engineering; Curriculum; Educational Assessment